Evaluation About The Tawjih-i Jihat Regulations Regulating Designation and Work Conditions of Religious Officer in Ottoman Empire - KAYA, UMUT (CUMHURIYET UNIV, FAC THEOLOGY, 2017)
Tanzimat was the period that important events had taken place for Ottoman Empire. In this study, an evaluation about Tawjih-i Jihat Regulations will be done. Tawjih-i Jihat Regulations are legal arrangements which regulate designation rules of religious officers in Ottoman Empire. There are three regulations which published in 9 February 1870 (Hijri 8 Zilkade 1286), 9 April 1873 (Hijri 10 Safer 1290) and 5 August 1913 (Hijri 12 Ramazan 1331). Accordingly, the transcription of 1913 Tawjih-i Jihat Regulation have been given after a comperative analysis of three regulations (1870, 1873 and 1913 Regulations) by comparing today conditions about religious officers. Especially, in this evaluation parts will have focused jihat exams (subject, measurement and evaluation, the question resources, types of questions, and etc.) and proficiency requirements.
Keywords: Ottoman; Jihat; Tawjih-i Jihat; Religious Officer; Proficiency Exam